2019
DOI: 10.1177/0284185119883391
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and diversity of spontaneous brain activity in functional dyspepsia subtypes

Abstract: Background Functional dyspepsia (FD) subtypes may differ in terms of pathophysiology, but the underlying mechanisms remain poorly understood. Purpose To explore spontaneous brain activity in two main FD subtypes, namely epigastric pain syndrome (EPS) and postprandial distress syndrome (PDS), using the amplitude of low-frequency fluctuation (ALFF). Material and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…These results also fitted the functional alteration in GM-related studies, such as decreased functional connectivity of insula (Sun et al, 2020); decreased GM density in the middle frontal gyrus, right precentral gyrus, and insula (Zeng et al, 2013); and decreased connectivity between insula and thalamus (Liu et al, 2018). Our former study also found altered amplitude of low-frequency fluctuation in insula and thalamus (Qi et al, 2020). Our results supported that the frontal lobe, insula, and thalamus were the key regions in FD patients.…”
Section: Discussionsupporting
confidence: 88%
“…These results also fitted the functional alteration in GM-related studies, such as decreased functional connectivity of insula (Sun et al, 2020); decreased GM density in the middle frontal gyrus, right precentral gyrus, and insula (Zeng et al, 2013); and decreased connectivity between insula and thalamus (Liu et al, 2018). Our former study also found altered amplitude of low-frequency fluctuation in insula and thalamus (Qi et al, 2020). Our results supported that the frontal lobe, insula, and thalamus were the key regions in FD patients.…”
Section: Discussionsupporting
confidence: 88%
“…Individual head translations, rotations, and the framewise displacement were calculated, and only one healthy control in this study was found to have excessive head motion. Second, the T1 structural image was co-registered to the functional image, then and then normalized to the standard Montreal Neurological Institute (MNI) space with Exponentiated Lie algebra (DARTEL) as in the study of Qi et al ( 2019 ). Third, the white matter signal and cerebrospinal fluid signal were also regressed out.…”
Section: Methodsmentioning
confidence: 99%
“…ALFF was computed with the same method as described in the previous study (Qi et al, 2019 ). After bandpass filtered (0.01–0.1 Hz) and detrended, the time course was transformed to the frequency domain with Fast Fourier Transform.…”
Section: Methodsmentioning
confidence: 99%
“…Non-invasive and high spatial and temporal resolution techniques, such as functional magnetic resonance imaging (fMRI), support brain–gut interaction studies based on human beings. For example, through fMRI techniques, studies have identified changes in brain activity in the medial prefrontal cortex, orbitofrontal cortex, cingulate gyrus, hippocampus, precuneus, and temporal pole in FD patients compared with healthy subjects ( Liu et al, 2013 ; Chen et al, 2018 ; Qi et al, 2020 ). Thus, the Rome criteria have defined FD as a disease with abnormal brain–gut interaction ( Drossman, 2016 ).…”
Section: Introductionmentioning
confidence: 99%